The implementation of crisis communication strategies by PLN UID Bali in handling the 2025 Bali Blackout - Fidyariska, Priskylia Jenia; Indrashwara, Decky Cipta (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
Crises in the public service sector not only require a technical handling strategy, but also include responsive and accountable communication aspects. This study aims to analyze the public communication strategy by PLN UID Bali in responding to the blackout incident that occurred on May 2, 2025. The incident resulted in a mass power outage for nearly twelve hours in most areas of Bali. The research method used a qualitative approach and a case study design. Data was collected through in-depth interviews with PLN UID Bali Public Relations and documentation of official PLN UID Bali social media uploads. The study's findings show that applying Situational Crisis Communication Theory (SCCT), PLN UID Bali adaptively manages the flow of information and public perception by combining four main strategies: deny, diminish, rebuild, and reinforce. The study also found that time is a crucial element in crisis communication. The speed of conveying valid information can suppress the potential to escalate public unrest. For this reason, updates to crisis communication SOPs have begun to be carried out, including planning to use digital-based monitoring devices to map public perception in real-time. In general, the success of crisis handling by PLN UID Bali depends not only on the technical aspects of service recovery but also on the effectiveness of public communication built on the principles of openness, empathy, and consistency.